2023
DOI: 10.3390/foods12061119
|View full text |Cite
|
Sign up to set email alerts
|

Microclimate and Genotype Impact on Nutritional and Antinutritional Quality of Locally Adapted Landraces of Common Bean (Phaseolus vulgaris L.)

Abstract: This study aimed to assess the impact of genotype, location, and type of cultivation (organic) on the nutrient and anti-nutrient components of seven large-seeded bean (Phaseolus vulgaris L.) populations. All genotypes were cultivated during 2014 and 2015 in randomized complete block (RCB) experimental designs in three areas of the Prespa region (Pili, Patoulidio, Agios Germanos) in Greece. Particularly, total protein (18.79–23.93%), fiber (7.77–12%), starch (40.14–55.26%), and fat (1.84–2.58%) contents were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Different genotypes and cultivation conditions greatly affect the level of non-nutritional factors in KB seeds. By comparing the changes in non-nutritional factors in KBs with different genotypes and cultivation conditions, it was found that trypsin inhibitors were most affected by cultivation conditions, and stress conditions significantly increased the expression of trypsin inhibitors in the vegetative and reproductive stages of KBs by 46.2% [48].…”
Section: Trypsin Inhibitormentioning
confidence: 99%
“…Different genotypes and cultivation conditions greatly affect the level of non-nutritional factors in KB seeds. By comparing the changes in non-nutritional factors in KBs with different genotypes and cultivation conditions, it was found that trypsin inhibitors were most affected by cultivation conditions, and stress conditions significantly increased the expression of trypsin inhibitors in the vegetative and reproductive stages of KBs by 46.2% [48].…”
Section: Trypsin Inhibitormentioning
confidence: 99%
“…On the other hand, it is well-known that agronomic factors such as the type and fertility of the soil, climatic variables, plant management, and cultivars used have an effect on the nutritional and functional value of common bean seeds (González et al, 2006;Uyanöz et al, 2007;Medina-Velo et al, 2017;Celmeli et al, 2018;Nicoletto et al, 2019;Philipo et al, 2020;Bosmali et al, 2023). However, sometimes there are discrepancies in the findings of different works studying the same aspect, which could be due to the difficulty of reproducing the tests and interactions among the various factors evaluated (genotype, climatic conditions, soil, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, although it seems clear that organic farming is a sustainable alternative to conventional farming, and its positive influence on some dry bean phytochemicals has been revealed, such as a higher content of phenolic compounds (Barański et al, 2014;Mastura et al, 2017;Barreto et al, 2021;Bosmali et al, 2023), what is certain that in other cases, the results are still inconclusive, as Barreto et al (2021) point out. One possible cause of this lack of consistency that should be pointed out is the fact that, on the one hand, there are in fact still very few works that study differences in organic and conventional production and, on the other, the works that do exist generally consist of a comparison of values for commercial samples, and do not take into account the diversity of factors like cultivated variety, environmental conditions, fertilizers, land management, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In rice, starch accumulation was inhibited, and amino acid accumulation was induced in grains during ripening by high temperatures [ 19 , 20 ]. Climate conditions have been reported to affect the quality of agricultural products such as asparagus [ 21 ], common beans [ 22 ], cherries [ 23 ], and pomegranates [ 24 ]. However, most of these studies used agricultural products that had been exposed to the same climate conditions throughout the study period and used agricultural materials such as shade or mulch.…”
Section: Introductionmentioning
confidence: 99%